PENGARUH SERVQUAL TERHADAP CITIZEN SATISFACTION (STUDI PADA PENGGUNA TRANS MAMMINASATA) - Harry Yulianto; Syarief Dienan Yahya (AkMen JURNAL ILMIAH, 2018)
The growth of city if it has not offset by the development of road infrastructure, so it has make congestion on some roads, then it has an impact toward time and economy. One of solution to overcoming the road transportation congestion is the provision adequate of mass transport that can interest people to leave the private vehicles and switch to public transport. An aims this research to examine the effect of servqual toward citizen satisfaction on Trans Mamminasata. This study was using a quantitative approach, with cross sectional design. Sampling technique in this study was using non probability sampling with purposive sampling method. Techniques of data collection for hypothesis test was using questionnaires with closed question. Variables was used in this study such us independent variables (servqual) and the dependent variable (citizen satisfaction). The independent variable consists of five dimensions, such us: reliability, responsiveness, tangibles, assurance, and empathy. In this study, the instrument validity test using Confirmatory Factor Analysis (CFA), and reliability test performed using cronbach's alpha correlation. There are six hypotheses in this study which test using different data analysis techniques, such us: simple linear regression (H1, H2, H3, H4, and H5), and multiple linear regression (H6). The results of this research showed that there were three rejected hypotheses (H1, H2, H3) and three accepted hypotheses (H4, H5, H6).